Early childhood education and teacher training: a reflection on teaching knowledge - Pereira, Meira Chaves [UNESP] (Univ Fed Sao Carlos, 2018)
This work had as objective to discuss the knowledge necessary to the practice of the teacher of basic education with emphasis on early childhood education. A review of specialized literature on three reflexive axes a) discussion of teachers' knowledge (TARDIF, 2002, GAUTHIER, 1998, SHULMAN, 2014), b) the construction of knowledge (BOURDIEU, 2003) and c) the reflective practice (SCHON, 1992). In the light of the unveiled considerations, it was possible to understand that some authors deal with teacher knowledge such as those arising from experience, the craft, the training and the curriculum. On the other hand, pedagogical knowledge of content, knowledge about how content is taught, highlighting the how to teach certain content or subject presented to a group of students in a given context, is characterized as a knowledge base of the teacher for teaching, for combining content with subject and pedagogy to the teaching exercise.
Keywords: Teacher knowledge; Knowledge construction; Child education